2023
DOI: 10.1097/md.0000000000033334
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of modified-Gustave-Roussy Immunity Score in resectable proximal gastric cancer

Abstract: The prognostic evaluation of GRIm score has been confirmed in many tumor species. The purpose of this study is to clarify the value of GRIm score in the prognostic evaluation of patients with resectable proximal gastric cancer. A single center retrospective study was conducted in 174 patients with proximal gastric cancer who underwent radical total gastrectomy. An in-depth analysis was carried out to explore the prognostic differences between high and low GRIm, and the influencing factors of disease-free survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Three studies were excluded at that stage: one study reported data on oesophageal cancer and two studies did not report relevant outcomes. Finally, eighteen studies that investigated the prognostic significance of lactate dehydrogenase (LDH) in gastric cancer were included in this review (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Study Selection Processmentioning
confidence: 99%
“…Three studies were excluded at that stage: one study reported data on oesophageal cancer and two studies did not report relevant outcomes. Finally, eighteen studies that investigated the prognostic significance of lactate dehydrogenase (LDH) in gastric cancer were included in this review (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Study Selection Processmentioning
confidence: 99%